Efficiency and durability of hyaluronic acid of different particle sizes as an injectable material for VF augmentation. (2nd December 2015) - Kim, Yeon Soo; Choi, Jae Won; Park, Ju-Kyeong; Kim, Yoo Suk; Kim, Hyun Jung; Shin, Yoo Seob; Kim, Chul-Ho
Abstract: Conclusion: The results of the present investigation suggest that modification of HA could improve efficiency and durability in augmentation laryngoplasty. Objectives: Injection laryngoplasty (IL) is one of the most suitable options for treatment of glottic insufficiency, which is caused by vocal fold (VF) paralysis, atrophy, or scarring. Hyaluronic acid (HA) is a widely used material for VF injection. This study was intended to evaluate the durability and efficiency of HA of different particle sizes for VF augmentation. Methods: Three types of HA, Restylane®, monophasic low-viscosity, and unequal particle-sized middle-viscosity HA were injected into the left VF of three groups with eight rabbits each. Results: After 6 and 10 weeks, the injected site was evaluated endoscopically, histologically, radiologically, and functionally. None of the 24 rabbits showed any signs of respiratory distress. Computed tomography (CT) images and endoscopic evaluation revealed sufficient augmented volume of the injected VF in all treated groups 6 weeks after the injection. Histological data at week 10 showed that unequal particle-sized HA did not migrate from its original injection site, while other HAs migrated to the periphery of the arytenoid cartilage. Videokymographic analysis showed more favorable vibrations of unequal particle-sized HA injected VF mucosa 10 weeks post-injection, compared to the other treatment groups.